Odpowiedzi

  • nnn
  • Początkujący
2009-10-15T20:46:40+02:00
1\3 x² - 27 = 0
x = 9

3/8x² = 0,(6)
x = ?

9x² +100 = 0
x= -10\9

x² + 4 = 2x² - 6
x = 2.5

5 - x² = x² + 3
x=2

(1-√2)x² =√2
x= 1

x²=(1 - x )(1 + x )
x² = 1² - x² (nie wykonalne)

( x - 1)² - 1 =0
x= 0

(2x + 3 )² = ( x - 3)²



2009-10-15T20:53:04+02:00
Odpowiedz w załączniku:)


(1-√2)x^ =√2
(1-√2)x^ -√2 = 0
x=1
2009-10-15T20:58:46+02:00
1. delta= b^2 - 4ac
delta= 0 - 4*1/3 *(-27)
delta= 4*9
delta = 36
x=(-b-pierwiastek z delty)/2a lub x=(-b+ pierwiastek z delty)/2a
x=(-pierwiastek z 36[bo b=0])(2*(1/3)) lub x=(pierwiastek z 36)/(2*(1/3))

x= -6/(2*(1/3)) lub x= 6/(2*(1/3))
x=-9 lub x=9
cdn
1 5 1